ધારો કે $\quad \sum \limits_{n=0}^{\infty} \frac{n^3((2 n) !)+(2 n-1)(n !)}{(n !)((2 n) !)}=a e+\frac{b}{e}+c,$ $a, b, c \in Z$ પુર્ણાકો છે.$e=\sum_{n=0}^{\infty} \frac{1}{n !} $ હોય તો $a^2-b+c$ ની કિમંત મેળવો.
$25$
$24$
$23$
$26$
${\log _4}18 = . . . .$
જો $A = {\log _2}{\log _2}{\log _4}256 + 2{\log _{\sqrt 2 \,}}\,2$ તો $A = . . . .$
જો ${\log _{10}}2 = 0.30103,{\log _{10}}3 = 0.47712$ તો ${3^{12}} \times {2^8}$ માં રહેલા અંકોની સંખ્યા મેળવો.
${81^{(1/{{\log }_5}3)}} + {27^{{{\log }_{_9}}36}} + {3^{4/{{\log }_{_7}}9}} = . . . .$
અસમતા ${5^{(1/4)(\log _5^2x)}}\, \geqslant \,5{x^{(1/5)(\log _5^x)}}$ નો ઉકેલ ગણ મેળવો